Optimization Design of Drivetrain of FSAE Racing based on ANSYS - Wang Yanshu (Jixie chuandong)
A set of method which applies to the design and optimization of the sprocket in FSAE racing drivetrain is presented. Focusing on the process of the 75 m straight line acceleration,after determining the parameters of the large sprocket,the maximum impact on the large sprocket is calculated. By using the ANSYS optimization module,the position and the size of the lightening holes are optimized to try to arrange rationally and lose weight on the basis of meeting intensity of use.